Book spreaders in the towns of Samogitian principality in the XVIII century - Elmantas Meilus (Knygotyra)
The free spread of Enlightenment books from Western Europe in the 18th century in the Samogitian principality (the books were presumably spread following the decision of sovereign Michał Korybut Wiśniowiecki issued in 1672) worried the leaders of the Catholic Church who were responsible for education in the Republic of Both Nations. For this reason, in 1743, the Samogitian bishop Antanas Tiškevičius banned the free book trade in his diocese and commissioned Juozas Stripeika and Martynas Maulevičius, living in Kražiai, with the task of regulating book selling. Antanas Tiškevičius' circular provides the following information: 1. In the 18th century, at least in its 2nd quarter, the book trade was a profitable business, which means that books were popular; 2. It is likely that until the mentioned time, books had been sold by traveling book sellers for whom that was their only occupation; 3. At the considered time, Samogitia received the most up-to-date literature from Western Europe.